الشعر الشعبي ودوره في تعزيز الهوية والانتماء: شعر نذير بلفضيل أنموذجا - عثماني، عمار (جامعة محمد الصديق بن يحيى جيجل, 2019)
Arabic poetry is distinguished by the characteristics that govern it and make it exclusive property of those who practice it, because the ancients said: "Poetry is the collection (Diwan) of the Arabs, which leads one to guess that one can to know the reality of the Arabs and the nature of their belonging and the identity of their acts and culture through poetry. And if this is so for standard classical Arabic poetry, the specificity of the structure in popular poetry, is crossed with the latter in what brings together the two genres namely the expression of the identity and the belonging, the difference existing only in representation, given that standard classical poetry is a link for the people while popular poetry is a link for the entire nation. It is in the light of this hypothesis that our study attempts to know the ideal way that popular poetry makes the best use of the concept of identity which has been so much a favorite subject for poets, speakers, journalists and politicians, and all those who are in touch with the letters, in a society that appeals to the identity of the homeland, and to the cohesion of its subjects which has become a necessity of social development. Thus we try through this article to define popular poetry and measure its role in the establishment and confirmation of national identity in Algerian society, using the poetry of Nadir BELFODHIL El-Relizani as a corpus to our study practice to show how this popular poetry works to achieve this goal, hence the question of the parameters of identity and belonging in Algerian popular poetry.
يتميز الشعر العربي عن غيره بخصائص تضبطه وتجعله ملكا لأهله، فقد قالوا قديما: إن الشعر ديوان العرب، ومعنى هذا أننا نستطيع التعرف على واقع العرب وخصوصية انتمائهم وهوية سلوكهم وثقافتهم من خلال الشعر. وإذا كان هذا ما يلزم الشعر الفصيح، فإن خصوصية البناء في الشعر العامي تشركه وتختلف معه، إذ إن يكمن في التعبير عن الهوية والانتماء، وأن الاختلاف يتمثل في أن الفصيح رابط أمة، والعامي رابط وطن. بناء على هذه الفكرة الافتراضية يأتي عملنا بغية معرفة الكيفية المثلى التي يسهم فيها الشعر الشعبي في خدمة موضوع الهوية. التي لطالما تغنى بها الشعراء والخطباء والصحفيون والسياسيون، وكل من يمتهن الكلمة، في مجتمع يناشد هوية الوطن، فأصبح تماسك أفراده من الأولويات التي تخدم بناء المجتمع. ومن ثمة فإن هذه الورقة العلمية تحاول أن تتوقف عند عن ماهية الشعر الشعبي ودور في تثبيت وإرساء معالم الهوية الوطنية في المجتمع الجزائري، وتتخذ من شعر نذير بلفضيل الغليزاني أنموذجا في التطبيق، من أجل الكشف عن الكيفية التي يعمل وفقها الشعر الشعبي لتحقيق هذا الموضوع، الأمر الذي يدعونا للاستفسار عن أبعاد الهوية والانتماء في الشعر الشعبي الجزائري.
Keywords: الأدب العربي -- الشعر العربي -- الشعر الشعبي -- الشعراء العرب -- الجزائر